How is Life in Extreme Environments? (2016)
Although humans have managed to adapt to various extreme environments thanks to technology, there are living beings who do it on their own, these are known as the extremophiles, who can live in places too salty, acidic, cold or warm thanks to their fascinating mechanisms and cellular functions.